Chirp-rate quasi-orthogonality based DSSS-CDMA system for underwater acoustic channel. (April 2020) - Yuan, Fei; Jia, Zhen-yu; Cheng, En
Abstract: Underwater network node positioning is a key supporting technology for underwater networks. Generally, nodes at known locations (anchor nodes) are used to transmit location information to the node to be located, and the node to be located performs location calculation according to the arrival time of the received information, which requires multiple access communication between the anchor nodes and the node to be located. In order to reduce the multiple access interference (MAI) and distinguish the information of different anchor nodes, it is necessary to study the underwater multiple access method. The GPS positioning system uses direct sequence spread spectrum code division multiple access(DSSS-CDMA) technology, and the positioning satellite transmits a signal formed by the BPSK modulation by transmitting a pseudo-random sequence (PN sequence) to the binary code sequence corresponding to the navigation message to the user equipment to be located. The underwater acoustic (UWA) channel has a complex multipath structure and Doppler effect, which causes a large interference to the communication system. Compared with narrowband communication, spread spectrum communication has a strong anti-interference ability, and can maintain the reliability of the communication system in the UWA channel. Based on this, this paper proposes a quasi-orthogonal Chirp-rate based DSSS-CDMA method under UWA channel, and carries out simulation analysis and experimental verification.